2010
DOI: 10.1016/j.ydbio.2010.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Akt1 causes heart defects and abnormal cardiomyocyte proliferation

Abstract: The PI3K-PDK1-PKB/Akt (PI3K, phosphoinositide-3 kinase; PDK1, phosphoinositide-dependent protein kinase 1; PKB, protein kinase B) signaling pathway plays a critical role in a variety of biological processes including cell survival, growth and proliferation, metabolism and organogenesis. Previously, we generated Akt1-deficient mice and found high neonatal mortality with unknown causes. Here we report that histological analysis of Akt1-deficient embryos and newborns revealed heart defects and decreased cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 39 publications
9
39
0
Order By: Relevance
“…Therefore it is postulated that the heart may contain some specific gene which is not expressed or stimulated abnormally in response to any factors such as mutagen. This postulation is in agreement with the echocardiographic study of Akt1 gene deficient mice model which revealed that deletion of Akt1 caused substantial activation of p38MAPK leads to abnormal cardiomyocyte proliferation [7]. Therefore, further genomic study of heart may focus some inputs to analyses the presence of specific gene which prevent abnormal proliferation of cardiac cells.…”
Section: Editorialsupporting
confidence: 83%
“…Therefore it is postulated that the heart may contain some specific gene which is not expressed or stimulated abnormally in response to any factors such as mutagen. This postulation is in agreement with the echocardiographic study of Akt1 gene deficient mice model which revealed that deletion of Akt1 caused substantial activation of p38MAPK leads to abnormal cardiomyocyte proliferation [7]. Therefore, further genomic study of heart may focus some inputs to analyses the presence of specific gene which prevent abnormal proliferation of cardiac cells.…”
Section: Editorialsupporting
confidence: 83%
“…Disruption of Akt1 in mice causes CHD with a reduction in cell proliferation. 39 Mutations in other genes related to cell growth such as Hes1, or apoptosis such as Alk5, have already been associated to CHD in animal models. Hes1 knockout mouse embryos display defects in proliferation at early developmental stages, which induce a reduction in cardiac neural crest cells and failure to completely extend the outflow tract.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols for hematoxylin and eosin (H&E) staining, Masson's trichrome staining, and immunofluorescence (IF) were as described previously (23,27). Briefly, heart samples were first washed with ice-cold phosphate-buffered saline (PBS) and then fixed in 4% paraformaldehyde (PFA) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The TUNEL (TdT [terminal deoxynucleotidyltransferase]-mediated dUTP nick end labeling) assay was performed as described previously (23,27). Briefly, sections were treated with proteinase K (20 g/ml) and incubated with TdT and biotinylated dUTP.…”
Section: Methodsmentioning
confidence: 99%